Ron's Roots

Algebra Level 3

Let α \alpha and β \beta be the roots of 3 x 2 + 4 x + 9 = 0 3 x^{2} + 4x + 9 = 0 . Then ( 1 + α ) ( 1 + β ) (1+ \alpha)(1 + \beta) can be expressed in the form a b \frac{a}{b} , where a a and b b are coprime positive integers. Find a + b a+b .

This problem is posed by Ron G.


The answer is 11.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

10 solutions

Eric Wibowo
May 20, 2014

(1+α)(1+β)=1+(α+β)+αβ. According to Vieta's Formulas: If α and β are the roots of ax^2+bx+c=0,then α+β= - b/a and αβ= c/a. So α+β= - b/a = -4/3 and αβ= c/a = 9/3=3. Hence (1+α)(1+β)=1+(α+β)+αβ=1+(-4/3)+3=8/3. 8/3 is the form of a/b. Therefore a+b=8+3=11.

Most submitted correct solutions were similar to this one, with an exception of a few "brute force" solutions, that used the formula for the roots of the quadratic equation.

Calvin Lin Staff - 7 years ago
Vardhman Jain
May 20, 2014

We know that quadratic equations are of the form ax^2 + bx +c=0 where sum of roots = - ( \frac {b}{a} ) and product of roots = \frac {c}{a}. Here, sum of roots = (alpha + beta) = - ( \frac {4}{3} ) and product of roots = ( alpha * beta ) = \frac {9}{3} On expanding (1 + aplha)(1 + beta) we get 1 + ( alpha + beta) + (alpha * beta) . Putting values in this equation from above, we get 1 - ( \frac {4}{3} ) + ( \frac {9}{3} ) . Solve it to get /frac {8}{3} which is 11 in terms of a + b.

Akram Shreim
May 20, 2014

(1+α)(1+β)=1+(α+β)+αβ=1-4/3+9/3=8/3 a=8 , b=3 , a+b=3

Diamantis Koreas
May 20, 2014

We know that the sum of the roots is -4/3 and their product 3. So (1+a)(1+b)= 1+a*b +a+b =4-4/3=8/3.

Nishant Sharma
May 20, 2014

Let S = α \alpha + β \beta and P = α \alpha β \beta

From Vieta's Formulae for sum and product of roots we obtain S = - 4 3 \frac{4}{3} and P = 9 3 \frac{9}{3} = 3

Let X = (1 + α \alpha ) (1 + β \beta )

= 1 + α \alpha + β \beta + α \alpha β \beta

= 1 + S + P

= 1 - 4 3 \frac{4}{3} + 3

= 8 3 \frac{8}{3} = a b \frac{a}{b}

Since a a and b b are co-prime positive integers, comparing from the final result we obtain a a + b b = 8 + 3 = 11 which is our answer.

Parth Kohli
May 20, 2014

Expanding ( 1 + α ) ( 1 + β ) (1 + \alpha)(1 + \beta) , we get 1 + α + β + α β 1 + \alpha + \beta + \alpha\beta . In the given polynomial 3 x 2 + 4 x + 9 3x^2 + 4x + 9 , a = 3 , b = 4 a = 3, b = 4 and c = 9 c = 9 . According to Vieta's Formula, α + β = b a = 4 3 \alpha + \beta = \frac{-b}{a} = -\frac{4}{3} and α β = c a = 9 3 = 3 \alpha\beta = \frac{c}{a} = \frac{9}{3} = 3 .

Hence, 1 + α + β + α β = 1 + ( 4 3 ) + 3 = 8 3 1 + \alpha + \beta + \alpha\beta = 1 + \left(\frac{-4}{3}\right) + 3 = \frac{8}{3} .

Since 8 8 and 3 3 are coprime, the answer is simply 8 + 3 = 11 8 + 3 = 11 .

Minh Ho Nhat
May 20, 2014

(1+α)(1+β)=1+α+β+αβ By Viete's Theorem ,we have: α+β= -4/3 αβ =9/3 So (1+α)(1+β)=1+(-4/3)+9/3=8/3 a+b=8+3 =11

Wei Jie Tan
May 20, 2014

For any given quadratic equation a x 2 + b x + c ax^2 + bx + c , the roots are

α \alpha = b + b 2 4 a c 2 a \frac{-b + \sqrt{b^2-4ac}}{2a}

β \beta = b b 2 4 a c 2 a \frac{-b - \sqrt{b^2-4ac}}{2a}

Hence

α \alpha + β \beta = b + b 2 4 a c 2 a \frac{-b + \sqrt{b^2-4ac}}{2a} + b b 2 4 a c 2 a \frac{-b - \sqrt{b^2-4ac}}{2a} = b + b 2 4 a c + ( b ) b 2 4 a c 2 a \frac{-b + \sqrt{b^2-4ac} + (-b) - \sqrt{b^2-4ac}}{2a} = 2 b 2 a \frac{-2b}{2a} = b a -\frac{b}{a}

α β \alpha\ \cdot \beta = b + b 2 4 a c 2 a b b 2 4 a c 2 a \frac{-b + \sqrt{b^2-4ac}}{2a} \cdot \frac{-b - \sqrt{b^2-4ac}}{2a} = ( b + b 2 4 a c ) ( b b 2 4 a c ) 4 a 2 \frac{(-b + \sqrt{b^2-4ac}) \cdot (-b - \sqrt{b^2-4ac})}{4a^2} = ( b ) 2 ( b 2 4 a c ) 2 4 a 2 \frac{(-b)^2 - (\sqrt{b^2-4ac})^2}{4a^2} = b 2 b 2 + 4 a c 4 a 2 \frac{b^2 - b^2 + 4ac}{4a^2} = 4 a c 4 a 2 \frac{4ac}{4a^2} = c a \frac{c}{a}

In the question, the formula is 3 x 2 + 4 x + 9 3x^2 + 4x + 9 .

Thus

( 1 + α ) ( 1 + β ) (1+\alpha) \cdot (1+\beta) = 1 + α + β + α β 1 + \alpha + \beta + \alpha \cdot \beta = 1 4 3 + 9 3 1 -\frac{4}{3} + \frac{9}{3} = 8 3 \frac{8}{3}

8 and 3 are coprime, hence the answer is 8 + 3 8+3 = 11 11

brute force solution

Calvin Lin Staff - 7 years ago
M Praveen Kumar
May 20, 2014

Given: 3 x 2 + 4 x + 9 = 0 3x^2+4x+9=0

We have Sreedhara's formula, x = b ± b 2 4 a c 2 a x= \frac { -b \pm \sqrt{b^2-4ac}}{2a}

i.e. x = 4 ± 4 2 4 3 9 2 3 x= \frac { -4 \pm \sqrt {4^2-4*3*9}}{2*3} = 4 ± 92 6 = \frac { -4 \pm \sqrt {-92}}{6} = 2 ± i 23 3 = \frac { -2 \pm i\sqrt {23}}{3}

Now , let α = 2 + i 23 3 \alpha = \frac { -2 + i\sqrt {23}}{3} and β = 2 i 23 3 \beta = \frac { -2 - i\sqrt {23}}{3}

Thus, ( 1 + α ) = 2 + i 23 3 + 1 (1+\alpha) = \frac { -2 + i\sqrt {23}}{3} +1 = 1 + i 23 3 = \frac { 1 + i\sqrt {23}}{3}

and ( 1 + β ) = 2 i 23 3 + 1 (1+\beta ) = \frac { -2 - i\sqrt {23}}{3} +1 = 1 i 23 3 = \frac { 1 - i\sqrt {23}}{3}

Therefore, ( 1 + α ) ( 1 + β ) = ( 1 + i 23 3 ) ( 1 i 23 3 ) (1+\alpha) (1+\beta) = (\frac{1+i\sqrt{23}}{3}) (\frac{1-i\sqrt{23}}{3}) ( 1 + α ) ( 1 + β ) = ( 1 2 i 2 ( 23 ) 2 3 3 ) = 1 + 23 9 = 24 9 = 8 3 = a b (1+\alpha) (1+\beta) = (\frac{1^2 - i^2 (\sqrt{23})^2}{3*3}) = \frac{1+23}{9} =\frac{24}{9}=\frac{8}{3}=\frac{a}{b}

therefore , a = 8 and b=3 and

a+b = 8+3 = 11.

brute force solution

Calvin Lin Staff - 7 years ago
Aneesh Kundu
Jun 2, 2014

f ( x ) = 3 ( x α ) ( x β ) = 3 x 2 + 4 x + 9 f(x)=3(x-\alpha)(x-\beta)=3x^2+4x+9

f ( 1 ) = 3 ( 1 + α ) ( 1 + β ) = 8 ( 1 + α ) ( 1 + β ) = 8 3 \Rightarrow f(-1)=3(1+\alpha)(1+\beta)=8 \Rightarrow (1+\alpha)(1+\beta)=\frac{8}{3}

a = 8 , b = 3 a + b = 11 \Rightarrow a=8,b=3 \Rightarrow a+b=\boxed{11}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...